Status and temporal change in the distribution of seagrass beds and coral reefs in the waters of Phu Quoc islands, Kien Giang province - Nguyen Van, Long; Tong Phuoc Hoang , Son (Vietnam Journal of Marine Science and Technology, 2023)
To assess the status and changes in the distribution of seagrass beds and coral reefs in Phu Quoc from 2005 to 2018, we utilized high-resolution multi-spectrum satellite images, aerial photographs, and Google maps. We collected data from three time periods: 2005 (using ASTER with 15 m resolution), 2010 (using SPOT5 with 10 m resolution), and 2018 (using SENTINEL-2 with 10 m resolution). We also conducted an accuracy assessment of 78 key sites in March-April 2019, representing corals (25 sites), seagrasses (28 sites), rocks (8 sites), and sand (12 sites) through SCUBA diving. The results showed that in 2018, the waters of Phu Quoc contained 513 ha of coral reefs and 10,035 ha of seagrass beds, with 290 ha of coral reefs and 9,185 ha of seagrass beds located within the Phu Quoc marine protected area. While the area of coral reefs remained stable between 2005 and 2018, the seagrass beds experienced a significant decline of 652 ha (6.1%), with most losses occurring at Bai Vong (501 ha; 4.69%), Ong Doi cape - Dam Ngoai island (55 ha; 0.52%), Mot Island and Vinh Dam (42 ha; 0.4% each), and Da Chong cape (12 ha; 0.12%). This decline is largely due to recent infrastructure development for community and tourism purposes, which has caused the degradation of seagrass beds.